2011
DOI: 10.1177/0023830910388017
|View full text |Cite
|
Sign up to set email alerts
|

Speaker Age and Vowel Perception

Abstract: Recent research provides evidence that individuals shift in their perception of variants depending on social characteristics attributed to the speaker.This paper reports on a speech perception experiment designed to test the degree to which the age attributed to a speaker influences the perception of vowels undergoing a chain shift. As a result of the shift, speakers from different generations produce different variants from one another. Results from the experiment indicate that a speaker's perceived age can i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
94
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 28 publications
8
94
2
2
Order By: Relevance
“…The research described in this section provides evidence that the social characteristics attributed to the speaker can influence how phones are perceived. This suggests that phonetic representations are indexed to non-linguistic information and that this non-linguistic information is accessed during speech processing (Strand 1999;Campbell-Kibler 2007;Drager 2011b). Additionally, given the subtle phonetic differences between variants, the results provide evidence that the phonetic representation contains rich detail that previously was assumed to be filtered out during speech perception, storing only an abstracted form in the mental representation.…”
Section: Experimental Sociolinguisticsmentioning
confidence: 70%
See 1 more Smart Citation
“…The research described in this section provides evidence that the social characteristics attributed to the speaker can influence how phones are perceived. This suggests that phonetic representations are indexed to non-linguistic information and that this non-linguistic information is accessed during speech processing (Strand 1999;Campbell-Kibler 2007;Drager 2011b). Additionally, given the subtle phonetic differences between variants, the results provide evidence that the phonetic representation contains rich detail that previously was assumed to be filtered out during speech perception, storing only an abstracted form in the mental representation.…”
Section: Experimental Sociolinguisticsmentioning
confidence: 70%
“…There is evidence that the perception of phonetic variables can also be affected by other social characteristics attributed to the speaker, including dialect area (Niedzielski 1999;Hay, Nolan & Drager 2006), socioeconomic status (Hay, Warren & Drager 2006), age (Hay, Warren & Drager 2006;Drager 2006;2011b), and ethnicity (Casasanto 2010). The centring diphthongs /iə/ and /eə/, as in the words near and square, are undergoing a merger in NZE.…”
Section: Experimental Sociolinguisticsmentioning
confidence: 99%
“…As well as the age effects shown in the studies of NZE near and square by Hay et al (2006b) and Warren et al (2007), Drager (2011) found that the speaker's perceived age influenced the categorization of vowels on a dress-trap continuum in NZE, a variety which has a well-established pattern of raising of the short front vowels. However, she found this effect only for older participants, which she conjectures may be linked to their greater experience of a range of speakers from different generations as well as to their greater exposure to the progression of the sound change.…”
Section: Introductionmentioning
confidence: 88%
“…More importantly, listeners do so even when merely told to imagine that the speaker is a man versus a woman (Johnson et al 1999). Similar effects of listeners' expectations regarding the identity of the speaker on their interpretation of the speaker's speech have been found with expectations regarding other indexical information, such as speaker's age, race, or even occupation (Drager 2005(Drager , 2011Koops et al 2008;Pexaman and Olineck 2002;Staum Casasanto 2008).…”
Section: The Role Of Input In Shaping Expectationsmentioning
confidence: 76%
“…Experience can also differ even within the same language community. Drager (2011) found that age expectations influence vowel perception in older but not younger participants, presumably because older adults had greater experience and awareness of the merger in progress in the community than the younger adults. Perhaps the most direct link between individual differences in experience and performance can be seen in a study that examined individual differences in people's community make-up (Lev-Ari & Peperkamp in press).…”
Section: The Role Of Input In Shaping Expectationsmentioning
confidence: 89%